Pengembangan Aplikasi Pemantauan Alat Berat Pertambangan menggunakan Teknologi Geofencing dengan Arsitektur MVP - Arif Luthfiansyah; Denny Sagita Rusdianto; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
MyVeego is product as system that offers location-based services to help bussiness to manage fleets and assets owned by the company with location visibility, status, diagnostics, and real-time in-depth analysis owned by PT. Astra Graphia Information Technology. Mining has a large area and makes a distance between 2 (two) areas that are focussed far apart and difficult to monitor and manage when conducting mining activities. However, MyVeego does not have a service or module that can monitor the visibility of the location, time, and status of mining vehicles in real-time. By integrating Geofencing technology, WebSocket, and built on the Model-View-Presenter architecture, it allows a system can know the movement of entering, exiting, and dwelling objects to a specified area by displaying location visibility in real-time. Requirements engineering is carried out as the initial phase of research to find out business processs and system requirements. The requirements engineering phase results in 19 (nineteen) functional requirements and 1 (one) non-functional requirements. These requirements are used as a basis in to conducting the design and implementation phases. System implementation is done by integrating GPS technology as the basis of a location-based system, Geofencing technology, and WebSocket technology on the Model-View-Presenter architecture with the Kotlin programming language on the Android platform. Furthermore, from the implementation phase, the testing phase is carried out the result of complexity number 5.3 for unit testing, complexity number < 10 for integration testing. The testing phase gives 100% validity results in all tests.